Hubungan Tingkat Pengetahuan Diabetes Melitus dengan Kepatuhan Diet pada Pasien Diabetes Melitus Tipe II di UPTD Puskesmas I Denpasar - Saniasih, Ni Kadek; Juanamasta, I Gede; Pamungkas, M. Adreng (Jurnal Pustaka Keperawatan (Pusat Akses kajian Keperawatan), 2026)
Diabetes mellitus has become a global problem that threatens public health and socio-economics. One of the management options for diabetes mellitus sufferers is to regulate a healthy diet through diet management, but currently many diabetes sufferers still find it difficult to change their lifestyle. This study aimed to determine the level of knowledge of diabetes mellitus and dietary compliance in patients with type II diabetes mellitus. This type of research is quantitative correlational with a cross-sectional approach. The sample size were 186 respondents with type II diabetes mellitus. The instruments used were the DKQ-24 (Diabetes Knowledge Questionnaire) questionnaire to measure the level of knowledge and the PDAQ-9 (Perceived Dietary Adherence Questionnaire) to measure dietary compliance. The results showed that the majority of respondents were in the moderate knowledge category (102 people (54.8%), and dietary compliance was in the compliant category (171 people (91.9%). The results of the analysis using the Pearson correlation test showed a significant relationship between the level of knowledge and dietary compliance (p < 0.05), with a correlation coefficient of 0.000 meaning that the level of knowledge is related to patient consistency in following the diet, thus increasing dietary compliance. The higher the patient's level of knowledge about their disease, the more likely they are to comply with the recommended diet